Antibiotic (Mis)Use in COVID-19 Patients before and after Admission to a Tertiary Hospital in Serbia - Aleksa Despotović; Aleksandra Barać; Teodora Cucanić; Ksenija Cucanić; Goran Stevanović (MDPI AG, 2022)
Antimicrobial resistance (AMR) is a global concern, and antibiotic use has risen throughout the COVID-19 pandemic. Up to 75% of COVID-19 patients are treated with antibiotics despite little evidence for their use. A retrospective study from 6 March 2020 (the start of the pandemic in Serbia) to 31 December 2021 was conducted at the Clinic for Infectious and Tropical Diseases, University Clinical Centre of Serbia. In total, 523 patients with a microbiological diagnosis of COVID-19 were included. Patient data were analysed, including antibiotic use before and after admission. Pre-admission use of antibiotics for COVID-19 treatment was documented in more than half of patients (58.1%), of which a third (34.1%) used more than one antibiotic. Macrolides, cephalosporins, and fluoroquinolones were mainly used, most frequently among patients aged between 31-45 years (75.2%). Prior antibiotic use was associated with a longer duration of illness at admission (8.8 vs. 5.7, p < 0.001), oxygen therapy upon admission (27.6% vs. 16.0%, p = 0.002), and a lower vaccination rate (60.7% vs. 50.7%, p = 0.04). When hospitalised, 72.1% of patients received antibiotics, primarily cephalosporins (71.9%). Significant efforts are needed to reduce antibiotic use in the community and improve prescribing rates by healthcare professionals.